Tunicate-mimetic nanofibrous hydrogel adhesive with improved wet adhesion. (1st July 2015) - Oh, Dongyeop X.; Kim, Sangsik; Lee, Dohoon; Hwang, Dong Soo
Graphical abstract: Abstract: The main impediment to medical application of biomaterial-based adhesives is their poor wet adhesion strength due to hydration-induced softening and dissolution. To solve this problem, we mimicked the wound healing process found in tunicates, which use a nanofiber structure and pyrogallol group to heal any damage on its tunic under sea water. We fabricated a tunicate-mimetic hydrogel adhesive based on a chitin nanofiber/gallic acid (a pyrogallol acid) composite. The pyrogallol group-mediated cross-linking and the nanofibrous structures improved the dissolution resistance and cohesion strength of the hydrogel compared to the amorphous polymeric hydrogels in wet condition. The tunicate-mimetic adhesives showed higher adhesion strength between fully hydrated skin tissues than did fibrin glue and mussel-mimetic adhesives. The tunicate mimetic hydrogels were produced at low cost from recyclable and abundant raw materials. This tunicate-mimetic adhesive system is an example of how natural materials can be engineered for biomedical applications.